Illegal Conduct After the Decision of the Constitutional Court Number 03/Puu-Iv/2006 On Corruption Crime - I Gusti Ngurah Agung Permata Dewa; Zuhro Nurindahwati; Kadek Dedy Suryana (Journal of Social Research, 2024)
One of the phenomenal formulations of the Article is "unlawfully" Article 2 paragraph (1) of the PTPK Law which in its explanation is interpreted as acts against formal and material laws, has experienced a shift in meaning with the issuance of the Constitutional Court Decision No. 03/IV-PUU/2006 which only recognizes acts against formal laws, while acts against material laws are seen as not meeting the principle of legality, However, the Supreme Court in several of its decisions disagreed with the concept of the Constitutional Court's decision, using the doctrine of "Sens Chair" where judges are obliged to explore the values of law and justice that live in society. Based on these provisions, the problem can be formulated, namely how to develop the meaning of unlawful acts before and after the Constitutional Court Decision No. 03/IV-PUU/2006 on the Crime of Corruption and how the validity of the Supreme Court's decision which does not apply the decision of the Constitutional Court No. 03/PUU-IV/2006 in several decisions. To analyze these problems, the theory of criminal acts, the theory of corruption crimes and the theory of unlawful acts are used. This type of research is a normative research with a legislative approach, a historical approach and a conceptual approach, the sources of legal materials used in this study are primary, secondary and tresier legal materials, the collection of legal materials used is a documentation study and using quantitative analysis. The Constitutional Court's Decision No. 03/PUU-IV2006 has annulled the explanation of Article 2 paragraph (1) of the Law on the Eradication of Corruption (PTPK Law), which adopts the concept of material law in its positive function. As a result of this decision, the concept of unlawfulness in the PTPK Law should be interpreted as a teaching of formal and material unlawfulness in its negative function. The principle of legality is the main principle in criminal law, which aims to protect human rights from the arbitrary attitude of the rulers. However, the Supreme Court interprets formal and material unlawful acts in their positive function, they can still ensnare the perpetrators of corruption crimes and punish the defendants based on existing laws and regulations.